CLINICAL SIGNIFICANCE OF INCIDENT HYPOKALEMIA AND HYPERKALEMIA IN TREATED HYPERTENSIVE PATIENTS IN ALLHAT - Alderman, Michael H (2012)
Concerns exist that diuretic-induced changes in serum potassium may have adverse effects in hypertensive patients. ALLHAT, a large practice-based clinical trial made it possible to examine consequences of observed changes in potassium during care in conventional practice settings. Normokalemic participants randomized to chlorthalidone versus amlodipine or lisinopril as first-step drug were stratified by year-1 potassium. Post-year-1 outcomes among hypokalemics (potassium<3.5mmol/L) and hyperkalemics (potassium>5.4mmol/L) were compared to normokalemics (potassium 3.5–5.4 mmol/L). Year-1 hypokalemia incidence was 6.8%; incidence in chlorthalidone (12.9%) differed from amlodipine (2.1%; p<0.001) and lisinopril (1.0%; p<0.01). Hyperkalemia incidence (2.0%) was greater in lisinopril (3.6%) than chlorthalidone (1.2%; p<0.01) or amlodipine (1.9%; p<0.01). Coronary heart disease occurred in 8.1% with hypokalemia, 8.0% with normokalemia, and 11.1% with hyperkalemia. Overall, mortality was higher in hypokalemics than normokalemics (Cox hazard ratio =1.21; 95% confidence interval=1.02–1.44) with statistically significant (interaction p<0.01) disparity in hazard ratios for the three treatment arms (hazard ratios: chlorthalidone=1.21, amlodipine=1.60, lisinopril=3.82). Hyperkalemia was associated with increased risk of combined cardiovascular disease (hazard ratio=1.58; 1.15–2.18) without significant treatment interactions. In conventional practice settings, the uncommon appearance of hyperkalemia was associated with increased cardiovascular disease risk. Hypokalemia was associated with increased mortality; however, the statistically significant heterogeneity in hazard ratios across treatment groups strongly suggests that the observed increase in mortality is unrelated to the specific effects of chlorthalidone. Thus, for most patients, concerns about potassium levels should not influence clinician’s decision about initiating hypertension treatment with low-moderate doses of thiazide diuretics (12.5–25 mg of chlorthalidone).